"Blank as the Faces on Coins": Currency and Embodied Value(s) in David Foster Wallace's The Pale King. Issue 1 (1st January 2016) - Severs, Jeffrey
ABSTRACT: This article reveals David Foster Wallace's subtle interest in U.S. currency, the various values—both civic and monetary—it embodies and inscribes, and their often visceral conflicts. The article interprets the oblique images of money in The Pale King as sites of both a materialist economics and a claim that money, seen clearly, is always relational rather than divisive—a fact this novel treats in the context of the social obligation to pay taxes.